2019
DOI: 10.1136/ebmental-2018-300062
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of group-based mindfulness-based stress reduction and cognitive behavioural therapy for the treatment and management of chronic pain: A systematic review and network meta-analysis

Abstract: QuestionThis review compares mindfulness-based stress reduction (MBSR) to cognitive-behavioural therapy (CBT) in its ability to improve physical functioning and reduce pain intensity and distress in patients with chronic pain (CP), when evaluated against control conditions.Study selection and analysisOvid MEDLINE, EmbaseClassic+Embase, PsycINFO and the Cochrane Library were searched to identify randomised controlled trials. The primary outcome measure was physical functioning. Secondary outcomes were pain inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
3
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 41 publications
4
89
3
4
Order By: Relevance
“…Known contribution of LTOT to depression and secondary outcome of reducing opioid use/dose 13 3. Comorbid depressive symptoms of mild to moderate severity (PHQ-9 score of [10][11][12][13][14][15][16][17][18][19] People with subsyndromal depressive symptoms (PHQ-9 = 5-9) are less likely to show an effect from any intervention 4. Understanding of English language; able to sit for 20-25 minutes without significant discomfort; be willing and able to attend all 4 training sessions of SSM/HEP, as well as 75% of follow-up sessions Ensure ability to participate in interventions which will be delivered in English only and mostly in a seated position Exclusion criteria 1.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Known contribution of LTOT to depression and secondary outcome of reducing opioid use/dose 13 3. Comorbid depressive symptoms of mild to moderate severity (PHQ-9 score of [10][11][12][13][14][15][16][17][18][19] People with subsyndromal depressive symptoms (PHQ-9 = 5-9) are less likely to show an effect from any intervention 4. Understanding of English language; able to sit for 20-25 minutes without significant discomfort; be willing and able to attend all 4 training sessions of SSM/HEP, as well as 75% of follow-up sessions Ensure ability to participate in interventions which will be delivered in English only and mostly in a seated position Exclusion criteria 1.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…(62) A recent meta-analysis found improvements in physical function, pain intensity, and depression for patients with chronic pain treated with CBT, but no evidence of a significant difference compared to those treated with MBSR. (63) In a RCT that compared CBT, relaxation response training, and arthritis education in those with RA, significant improvements in symptoms, but not in pain, were noted at 12 month follow up. (64) There was not a significant change in levels of anxiety and depression as measured by the Rand Mental Health Inventory (MHI) in the CBT group.…”
Section: Mindfulness Based Interventions (Mbis)mentioning
confidence: 99%
“…In terms of efficacy, a recent systematic review demonstrated moderate effects for meditation and pain (effect size, 0.33), depression (effect size, 0.30) and anxiety (effect size, 0.38) [17]. Several systematic reviews examining meditation interventions specifically in the chronic pain population have reported small but consistent improvements in pain, function and depression [18][19][20][21]. Meditation is commonly sought out by diverse people living with depression and chronic pain and the intervention is well received in these populations [22][23][24].…”
Section: Introductionmentioning
confidence: 99%